Experimental study on pore structure evolution of high volatile bituminous coal with thermal treatment. (April 2022) - Shi, Qingmin; Kou, Bingyang; Sun, Qiang; Jia, Hailiang
Abstract: Pores and cracks are the main flow channels of coal, which affects the fluid migration and their reactions under high temperature. In this paper, high volatile bituminous coal in Ordos Basin was used to conduct the heating treatment experiments in N2 atmosphere. The results show that: (1) Pore evolution always occurred in the vitrinite that displays swelling, shrinkage, and rheology accompanying with pores creating, expanding, merging, collapsing and nesting. (2) The thermal evolution of pores presents three stages: in the initial stage, micropore remain occupied the main body before 300 °C; and in the middle stage, the mesopore and macropore displayed gradual increase ranging from 300 °C to 600 °C; and in the last stage, the micropores increased again and showed abundant porosity after 600 °C. Accordingly, the fractal dimension shown firstly decrease, and then increase corresponding to pores coalition and nesting. (3) The pore evolution is controlled by the thermal weight loss. The increase of weight loss rate is corresponding to the increase in mesopore and macropore and decrease in fractal dimension.